Technologization of Educational Standards and the Triple Hegemony of Cultural Inequality: Perspectives from Digital Education Internationalization - LiPeng, Wang; Wai Yie, Leong; Feng, Yang Yang (INTI International University, 2025)
This study employs systematic literature analysis and multi-case comparison to investigate how the technologization of educational standards generates cultural inequality in the process of digital education internationalization. The analysis of 127 publications (2018–2023) yields three major findings: (1) Western-centric classification dominates nearly 90% of MOOC courses; (2) cultural conflicts account for a 31% dropout rate among Middle Eastern learners in virtual exchanges; and (3) China’s dual-narrative strategy significantly enhances cross-cultural acceptance (+41%). By introducing the Cultural Alienation Index (CAI), the study quantifies digital cultural inequality and validates its explanatory power through cross-regional cases. The findings contribute a triple-hegemony model (infrastructure, algorithms, knowledge output) and propose decolonization strategies, offering both theoretical insights and practical pathways for equitable digital education governance.